(untitled) (ІННОВАЦІЙНА ЕКОНОМІКА, 2021)
Неміш Д.В., Гуменюк М.М., Баланюк І.Ф., Шеленко Д.І. ПЕРСПЕКТИВИ РОЗВИТКУ МАЛИХ АГРАРНИХ ПІДПРИЄМСТВ РЕГІОНУ У КОНТЕКСТІ ФОРМУВАННЯ РИНКУ ЗЕМЛІ Мета. Розкриття перспектив розвитку малих аграрних підприємств з огляду на трансформаційні процеси, що відбуваються у контексті формування ринку землі. Методика дослідження. Теоретико-методологічною основою дослідження стали законодавчі та інші нормативно-правові акти, наукові праці вітчизняних і зарубіжних учених із питань, які присвячені проблемам функціонування ринку землі та розвитку малих підприємств аграрного сектору. Для досягнення поставленої мети використовувались наступні загальнонаукові та спеціальні методи: абстрактно-логічний - під час формування теоретичних узагальнень, припущень, формування висновків; аналізу та синтезу – при оцінюванні розвитку малого аграрного підприємництва та функціонування ринку землі; порівняльного аналізу – для зіставлення економічних показників у часі та просторі; графічний – при наочному відображенні динаміки і структурних змін щодо розподілу земельного фонду за формами власності. Результати дослідження. Розглянуто соціально-економічні передумови трансформації структури земельного фонду за формами власності. Виділено основні стримуючі чинники розвитку ринку земель сільськогосподарського призначення. Розкрито заходи державної підтримки малих аграрних підприємств в процесі купівлі землі. Показано рівень ефективності функціонування ринку землі з моменту його запуску. Наведено основні позитивні аспекти та проблеми, пов’язані із формуванням ринку землі. Досліджено зарубіжний досвід впливу функціонування ринку землі на розвиток малих аграрних підприємств. Наукова новизна результатів дослідження. Поглиблено обґрунтування залежності розвитку малого аграрного підприємництва від рівня розвитку ринку землі. Практична значущість результатів дослідження. Впровадження розроблених пропозицій дасть змогу активізувати розвиток малих аграрних підприємств в умовах функціонування ринку землі і за державної підтримки вони отримають очевидні переваги. Ключові слова: мале аграрне підприємство, ринок землі, земля, земельні відносини, регіон, земельна реформа. Nemish D.V., Humeniuk М.M., Balaniuk I.F., Shelenko D.I. PROSPECTS FOR THE DEVELOPMENT OF SMALL AGRICULTURAL ENTERPRISES OF THE REGION IN THE CONTEXT OF LAND MARKET FORMATION Purpose. The purpose of the article is to reveal the prospects for the development of small agricultural enterprises in view of the transformation processes taking place in the context of land market formation. Methodology of research. Theoretical and methodological basis of the study were legislative and other regulations, scientific works of domestic and foreign scientists on issues related to the functioning of the land market and the development of small enterprises in the agricultural sector. The following general scientific and special methods were used to achieve this goal: abstract and logical method in the formation of theoretical generalizations, assumptions, conclusions; analysis and synthesis in assessing the development of small agricultural entrepreneurship and the functioning of the land market; comparative analysis to compare economic indicators in time and space; graphic method with a visual reflection of the dynamics and structural changes in the distribution of land by ownership. Findings. The research is devoted to a topical issue concerning the prospects for the development of small agricultural enterprises in the context of land market formation. The article pays special attention to aspects of land reform implementation The social and economic preconditions of transformation of the structure of the land fund by forms of ownership are considered. The main restraining factors of agricultural land market development are highlighted. Measures of state support of small agricultural enterprises in the process of land purchase are revealed. The level of efficiency of the land market since its launch is shown. The main positive aspects and problems related to the formation of the land market are presented. The foreign experience of the influence of the land market functioning on the development of small agricultural enterprises is studied. Originality. The substantiation of the dependence of the development of small agrarian entrepreneurship on the level of development of the land market is deepened. Practical value. The implementation of the developed proposals will allow to intensify the development of small agricultural enterprises in the conditions of the land market functioning. It is established that with the support of the state, small agricultural enterprises will receive obvious advantages of development. Key words: small agrarian enterprise, land market, land, land relations, region, land reform.